Are UK alcohol industry political donations intended to influence public health policies? – Analysis of publicly available data on donations and lobbying. (17th August 2021) - Acton, Crispin; Hawkins, Benjamin
Abstract : Transnational alcohol corporations seek to influence public health policies in ways reminiscent of the tobacco industry. Relatively little is known, however, about the extent of such activities in the alcohol sector, particularly their use of political donations. This study analyses data from the UK Electoral Commission on donations and from Transparency International UK on UK Government Ministerial meetings. Further research is needed to establish whether donations contribute to the disproportionate exposure of Ministers to alcohol industry lobbying. However, our combination of data on UK alcohol industry donations with data on lobbying provides important new evidence. Most larger company donors are active in lobbying and a significant minority of companies meeting Ministers are donors.